Mobility Between Heterogeneous Networks: Integration and Evaluation - Aguiar, R. L. (2007)
This paper presents a network architecture able to provide seamless and ubiquitous communication across multiple and heterogeneous technologies. It addresses seamless mobility with quality of service and authorization services in order to support multimedia traffic in a 4G network. The paper addresses the description of the mobility architecture, the integration effort performed in the framework of the IST-Daidalos project, and comments on the evaluation process used to assess the performance of the proposed architecture. We show that this architecture, supporting both mobile terminal and network initiated handovers, is able to prepare all the handover process in the new network, authorized in terms of the profile of the users and the resources available on the new network. In terms of the integration process, it has been significantly difficult in such a complex network: the integration of all the mobility related modules was a cumbersome process, and several issues appeared during this process, such as Mobile IPv6 implementation instability and different programming styles. In terms of the performance results achieved, we showed that this architecture is able to assure fast handover of mobile terminals with ongoing communications, with small handover timings and losses during handover.